Peer support and reminiscence therapy for people with dementia and their family carers: a factorial pragmatic randomised trial - Charlesworth, Georgina; Burnell, Karen; Crellin, Nadia; Hoare, Zoe; Hoe, Juanitia; Knapp, Martin; Russell, Ian; Wenborn, Jennifer; Woods, Bob; Orrell, Martin (BMJ, 2016)
Objective: The objective of this study was to evaluate peer support and reminiscence therapy, separately and together, in comparison with usual care for people with dementia and their family carers. Design: Factorial pragmatic randomised trial, analysed by treatment allocated, was used for this study. Setting: The trial ran in Community settings in England. Participants People with dementia and their family carers were the participants. Interventions: Treatment as usual (TAU) plus one of the following: one-to-one peer support to family carers from experienced carers (Carer Supporter Programme; CSP), group reminiscence therapy (Remembering Yesterday, Caring Today; RYCT) for people with dementia and carers, both or neither. Main outcome measures: Primary outcomes included health-related quality of life (SF-12) for carers and quality of life (QoL-AD) for people with dementia; secondary outcomes included quality of relationship for carers and people with dementia; both were collected by blinded assessors at baseline, 5 and 12 months (primary end point). Results: Of 291 pairs recruited, we randomised 145 (50%) to CSP (71% uptake) and 194 (67%) to RYCT (61% uptake). CSP and RYCT, separately or together, were not effective in improving primary outcomes or most secondary outcomes. For CSP versus ‘no CSP’, adjusted difference in means was 0.52 points on the SF-12 (95% CI −1.28 to 2.32) and −0.08 points on the QoL-AD (95% CI −1.70 to 1.56). For RYCT versus ‘no RYCT’, the difference was 0.10 points on the SF-12 (95% CI −1.72 to 1.93) and 0.51 points on the QoLAD (95% CI −1.17 to 2.08). However, carers reported better relationships with the people with dementia (difference 1.11, 95% CI 0.00 to 2.21, p=0.05). Comparison of combined intervention with TAU, and of intervention received, suggested differential impacts for carers and persons with dementia. Conclusions: There is no evidence from the trial that either peer support or reminiscence is effective in improving the quality of life. Trial registration number: ISRCTN37956201; Results